Lupinus mutabilis: Composition, Uses, Toxicology, and Debittering. Issue 9 (3rd July 2016) - Carvajal-Larenas, F. E.; Linnemann, A. R.; Nout, M. J. R.; Koziol, M.; van Boekel, M. A. J. S.
Abstract : Lupinus mutabilis has protein (32.0–52.6 g/100 g dry weight) and lipid (13.0–24.6 g/100 g dry weight) contents similar to soya bean (Glycine max). The Ω3, Ω6, and Ω9 contents are 1.9–3.0, 26.5–39.6, and 41.2–56.2 g/100 g lipid, respectively. Lupins can be used to fortify the protein content of pasta, bread, biscuits, salads, hamburgers, sausages, and can substitute milk and soya bean. Specific lupin protein concentrates or isolates display protein solubility (>90%), water-absorption capacity (4.5 g/g dry weight), oil-absorption capacity (3.98 g/g), emulsifying capacity (2000 mL of oil/g), emulsifying stability (100%, 60 hours), foaming capacity (2083%), foaming stability (78.8%, 36 hours), and least gelation concentration (6%), which are of industrial interest. Lupins contain bitter alkaloids. Preliminary studies on their toxicity suggest as lethal acute dose for infants and children 10 mg/kg bw and for adults 25 mg/kg bw. However, alkaloids can also have medical use for their hypocholesterolemic, antiarrhythmic, and immunosuppressive activity. Bitter lupins can be detoxified by biological, chemical, or aqueous processes. The shortest debittering process requires one hour. This review presents the nutritional composition of lupins, their uses (as food, medicine, and functional protein isolates), toxicology, and debittering process scenarios. It critically evaluates the data, infers conclusions, and makes suggestions for future research.